Pesquisa de protozoários Apicomplexa em ostras Crassostrea rhizophorae, Guilding, 1828 (Bivalvia: Ostreidae) da Baía de Todos os Santos – Bahia - Santos, Sofia Aline Amaral (2014)
The presence of oocysts of pathogenic protozoa in coastal waters resulting from the introduction of humans and animals contaminated feces has been recorded in different regions of the world. Bivalve molluscs such oysters can filter and retain in their tissues encysted protozoa and so act as potential transmitter of parasitic forms capable of causing diseases like toxoplasmosis and cryptosporidiosis. The aim of this study was to detect natural contamination in oysters of the species Crassostrea rhizophorae, grown in areas at the influence of de Todos os Santos Bay, Apicomplexa protozoan (Cryptosporidium and Toxoplasma gondii). A total of 615 oysters were collected from five points in two municipalities in the period from January to April 2013. Gills and digestive glands were dissected and grouped in pools of 3 animals, then resulted in 205 samples of gills and 205 samples of glands. For the molecular detection in tissue samples, DNA was extracted, then a nested-PCR was performed for the detection of genetic material of Cryptosporidium and another for detection of Sarcocystidae in order to amplify fragments of 600 and 290 base pairs, respectively. There was no DNA detection of Cryptosporidium in samples analysed. Genetic material compatible to T. gondii was amplified in 32 (7,8%) oyster tissue samples, and there are significant differences in the presence of positivity at two points of collecting. One of the factors that may be related with this finding is the proximity of these points to a location of soils washing containing feces of animals from farms. With these results we can infer that there is contamination of the aquatic environment and a risk of transmission of oocysts through consumption of oysters produced in these regions, which is an alert to the public health system.